(untitled) (Praxis Educativa, 2023)
The article is framed in a study of multiple cases, carried out in the educational region IX of the Province of Buenos Aires-Argentina, oriented to the analysis of the continuities and discontinuities of the school trajectories in the primary/secondary and secondary/superior transitions, from the analysis of the assessment. This work presents the results obtained from the study of one of the cases, on the ways of mathematics assessment between the last year of primary school and the first year of secondary school. The point of view of the teachers, the perceptions of students and the comparative analysis of school normative documents (curricular design and academic regime of each level) were taken into account. The work allows to illustrate the multiple dimensions at stake in the passage from one level to another and suggests some topics to improve the conditions that guarantee continuous school trajectories.